Safeguarding the deep-Sea Marine ecosystem: a critical analysis of the legal framework governing the impacts of the upstream Petroleum Sector on the deep-sea marine ecosystems and coastal communities in South Africa - Sehlabo, Mpho Lydia (Institute of Marine and Environmental Law, 2026)
The deep sea is a vast and largely unexplored environment, home to unique and diverse marine ecosystems. However, the increasing global demand for oil and gas has led to a surge in extraction activities in the deep ocean. These activities while essential for meeting energy demands, pose significant threats to the fragile deep-sea ecosystems. These ecosystems distinctive biodiversity which includes indigenous habitats and species are at risk from disruptions brought on by oil and gas exploration survey, drilling, and pollution. It has been demonstrated that the deep-sea marine ecosystems physical, biological, and ecological features have little resilience to the effects of oil and gas extraction. Certain marine species die due to the damaging effects of the environment on their ecosystems, which may eventually lead to a reduction in population and eventual extinction. Moreover, humans consume some marine animals, like fisheries, which makes them susceptible to these environmental effects. Hence, the need for effective and robust legal frameworks to govern oil and gas activities and protect the deep-sea environment and affected coastal communities. This mini-dissertation analysed whether the primary legal frameworks have been adequately designed to govern the environmental impacts of oil and gas extraction on the deep-sea marine ecosystems and coastal communities. It investigated the prominent environmental impacts of oil and gas activities on the marine ecosystems, provided an overview of the existing marine legal frameworks and proposed legal reforms and policy recommendations to advance the protection of the deep-sea marine ecosystems and affected communities in South Africa. This thesis contended that a multifaceted strategy, including more robust international agreements, harmonized national rules, mandatory industry standards, and improved monitoring and enforcement procedures, are needed to mitigate the negative environmental impacts on these key marine environments and affected communities.